Hand to type : scripts, hand-lettering and calligraphy. - Middendorp, Jan, 1956- (Berlin : Gestalten, 2012)
Although, or perhaps because, most of us write less and less by hand, our fascination for handwritten letterforms is growing. Typeface designers who specialize in traditional, charming, or spectacular lettering with a handmade look have become role models for today's young typographers and graphic design students. Script fonts--digital type families based on handwriting--are among the most sought on the typography market today. Scripts from the past, be it 18th-century formal calligraphy or advertising headlines from the 1960s, are being digitized and turned into OpenType programming. The love of the hand-written look is nothing new. Even the oldest printed books pretended to be something unique and not a machine-made mass product. Hand to Type is a collection of some of the best work by today's lettering artists in the fields of hand-made and digital script forms. The book includes texts about outstanding designers and contains a series of expert chapters outlining the principles of script forms that may be lesser known to most western typographers--from the German S tterlin to Arabic and Asian scripts. Hand to Type also traces script fonts back to some of the earliest examples: hand-lettering as a sign of authenticity, or printing type made to look like formal writing.